REKONSTRUKSI PERLINDUNGAN HUKUM TENAGA KERJA INDONESIA (TKI) DALAM PERSPEKTIF UU NO. 39 TAHUN 2004 TENTANG PENEMPATAN DAN PERLINDUNGAN TENAGA KERJA INDONESIA DI LUAR NEGERI YANG BERBASIS NILAI KEADILAN - Endar Susilo (Fakultas Hukum Universitas Wahid Hasyim, 2016)
Limitations minimum age for Indonesian workers abroad pose a problem, especially for workers who want to work in the non-formal as a housekeeper for prospective workers abroad wanted to be able to work abroad while their ages are not yet qualified in the country of destination , The problems of this study are (1) Why legal protection workers who were sent abroad had not been effective, (2) How the constraints of legal protection workers who were sent abroad at this time, (3) How is the reconstruction of legal protection protection of Indonesian labor law were sent abroad based on values of justice. The research method uses sociological juridical approach. Data collection techniques with interviews, observation, and documentation. Data were analyzed using interactive analysis method.The results of this study were (1) the ineffectiveness of legal protection for migrant workers, especially migrant workers abroad is due: The Role of Diplomacy Indonesia are weak because many of the problems migrant workers who have not received the attention or significant advocacy and thorough, weak law guaranteeing migrant workers with problems outside country, the government is not able to create jobs in Indonesia, Indonesia Indonesian representatives existence can not function optimally, lack of bilateral agreements between Indonesia and receiving countries migrant workers. (2) Constraints faced in the legal protection for workers or migrant workers today are: Low level of legal awareness prospective migrants / migrant workers, law enforcement weak, Weak surveillance systems workers, Reconstruction of the legal protection of migrant workers outside the country in accordance with the values of justice are in: Article 35 with the changes: Aged at least 18 (eighteen) years for prospective migrant workers who will be employed in both formal and informal (individual users), Article 42 with the changes added: (e) Provide sufficient knowledge about morals, manners, morals, and religion more deeply to potential migrant workers, Article 51 with the changes: (f) Passports can be issued by all the immigration office, which includes a written PPTKIS that processed and dispatched, Article 76 with changes in: (d) Handling and visas as well as the process requirements keberangatan others, (e) Require compensation to prospective migrants if for prospective workers is not so go abroad, Article 90 with changes in: (a) Provide guidance and advocacy for workers ranging from pre-placement, term placement and after placement by establishing legal aid (LBH) migrant workers in every region of the Republic of Indonesia, Article 95 with changes in: (10) Contribute to become law enforcement officers for workers, prospective workers and PPTKIS that can be served as investigator, investigator, and claimant to the achievement of a justice, Articles 105 and 106 with the changes: workers who go abroad can not be set off individually or independently migrant workerKeywords: Law Protection, Indonesian Workers Abroad, Justice